Peningkatan Keterampilan Menulis Cerita Sederhana dengan Menerapkan Metode Latihan Terbimbing dan Media Teks Lagu - Sujono Sujono (Departement of Mathematics Education, 2021)
This study aims to improve students' simple story writing skills by applying guided training methods and utilizing song text media. The subjects of this research were 37 students of class III-A with the research location at SD Negeri Wonokusumo VI / 45 Surabaya. This research was conducted through a two-cycle action mechanism. Based on data analysis, from this study it can be concluded that the Skills of Writing Simple Stories for Grade III-A students of SD Negeri Wonokusumo VI / 45 Surabaya increased by 20.44% after participating in learning Simple Story Writing through guided training methods with song text media. The average result of the pre-action Simple Story Writing test was 61 (rounding down from 61.30) and in the first cycle the average result was 69 (rounding up from 68.62) then in cycle II the average results were obtained. an average of 77 (the result is rounded down from 77.05) or an increase of 15.75% from cycle I. The average result of the Simple Story Writing test score shows that learning Simple Story Writing through the guided practice method with song text media on Class III-A students of SD Negeri Wonokusumo VI / 45 Surabaya can improve and succeed.